Step
*
1
1
1
1
of Lemma
decidable__reducible
1. a : ℕ
2. ¬(a = 0 ∈ ℤ)
3. b : ℤ-o
4. c : ℤ-o
5. ¬(b ~ 1)
6. ¬(c ~ 1)
7. a = (b * c) ∈ ℤ
⊢ ∃b,c:ℕa + 1. ((¬(b ~ 1)) ∧ (¬(c ~ 1)) ∧ (a = (b * c) ∈ ℤ))
BY
{ Assert ⌜a = (|b| * |c|) ∈ ℤ⌝⋅ }
1
.....assertion..... 
1. a : ℕ
2. ¬(a = 0 ∈ ℤ)
3. b : ℤ-o
4. c : ℤ-o
5. ¬(b ~ 1)
6. ¬(c ~ 1)
7. a = (b * c) ∈ ℤ
⊢ a = (|b| * |c|) ∈ ℤ
2
1. a : ℕ
2. ¬(a = 0 ∈ ℤ)
3. b : ℤ-o
4. c : ℤ-o
5. ¬(b ~ 1)
6. ¬(c ~ 1)
7. a = (b * c) ∈ ℤ
8. a = (|b| * |c|) ∈ ℤ
⊢ ∃b,c:ℕa + 1. ((¬(b ~ 1)) ∧ (¬(c ~ 1)) ∧ (a = (b * c) ∈ ℤ))
Latex:
Latex:
1.  a  :  \mBbbN{}
2.  \mneg{}(a  =  0)
3.  b  :  \mBbbZ{}\msupminus{}\msupzero{}
4.  c  :  \mBbbZ{}\msupminus{}\msupzero{}
5.  \mneg{}(b  \msim{}  1)
6.  \mneg{}(c  \msim{}  1)
7.  a  =  (b  *  c)
\mvdash{}  \mexists{}b,c:\mBbbN{}a  +  1.  ((\mneg{}(b  \msim{}  1))  \mwedge{}  (\mneg{}(c  \msim{}  1))  \mwedge{}  (a  =  (b  *  c)))
By
Latex:
Assert  \mkleeneopen{}a  =  (|b|  *  |c|)\mkleeneclose{}\mcdot{}
Home
Index